COMPARISON OF THE EFFECTS OF PAPAIN AND VITAMIN A ON CARTILAGE : I. THE EFFECTS IN RABBITS - Thomas, Lewis (The Rockefeller University Press, 1960)
The administration of large amounts of vitamin A to rabbits has been shown to result in depletion of cartilage matrix. The normal basophilic, metachromatic, and Alcian blue staining properties of the matrix are lost, especially in articular and epiphyseal cartilage. The cartilage cells remain intact, but are reduced in size. These changes sometimes appeared as early as 48 hours after the initiation of daily injection of 1 million units of vitamin A, and were usually well established by 5 days. Some rabbits failed to show changes in cartilage, even after 5 daily injections. Increased amounts of material presumed to be chondroitin sulfate were present in the sera of vitamin A-treated rabbits, usually by 72 hours after the first injection. This was demonstrated by a turbidimetric procedure using hexamminecobaltic chloride. In rabbits given sulfur-35 (Na(2)S(35)O(4)) 5 days before the initiation of vitamin A treatment, it was shown that sulfur-35 was lost from articular and epiphyseal cartilage. This was associated with an increase in the non-dialyzable sulfur-35 in both serum and in the cobalt-precipitable material. These rabbits also excreted more sulfur-35 than rabbits not given vitamin A. There was a reduction in sulfur-35 activity in chondromucoprotein extracted from the ear cartilage of vitamin A-treated rabbits. The changes are interpreted as indicating that the administration of large amounts of vitamin A to rabbits results in removal of chondroitin sulfate from cartilage matrix. The administration of small amounts of crude papain causes histologic changes in cartilage that are remarkably similar to those seen in vitamin A-treated rabbits. The possibility is suggested that the changes in cartilage produced by administration of vitamin A to rabbits may be the result of activation of a proteolytic enzyme or enzymes, with properties similar to those of papain.